Molecular mechanisms of plant steroids and study of their interaction with nuclear receptors in prostate cancer cells - Huskova, Zlata; Steigerova, Jana; Oklestkova, Jana; Rarova, Lucie; Kolar, Zdenek; Strnad, Miroslav (Food and chemical toxicology, 2020)
Plant hormone brassinosteroids (BRs) have multiple important functions in plants. They have also been found to exhibit anti-tumor, anti-angiogenic and anti-proliferative activity. The experimental part of this article describes the effects of BR biosynthetic precursors on prostate cancer cells. The experiments were performed with LNCaP and DU-145 prostate cancer cell lines. These were cultivated and treated with tested BRs in different concentrations and time intervals. The tested compounds were found to affect cell viability, nuclear receptor expression, cell cycle and apoptosis in the tumor cells. IC50 concentrations were determined based on MTT test and the two most active compounds (cathasterone and 6-oxocampestanol) were used in the next experiments. Cathasterone was the most effective of all tested compounds and effectively inhibited integrity of cell spheres. It was found that both BRs had no significant effect on the cell cycle in LNCaP at IC50 concentration, while in DU-145 a significant block in G0/G1 phase after the BR treatment was observed. The effect of BRs on the nuclear steroid receptors was manifested by changes in their expression and localization. BRs demonstrated their significant effect on prostate cancer cells and the compounds have potential used in anticancer drug research and cancer treatment.
Keywords: apoptóza; Cell Line, Tumor; Apoptosis; Prostate cancer; Brassinosteroids; Cell Cycle; lidé; Antineoplastic Agents; protinádorové látky; nádory prostaty; Prostatic Neoplasms; buněčný cyklus; Male; Receptors, Steroid; Apoptosis Regulatory Proteins; proteiny regulující apoptózu; Nuclear receptors for steroid hormones; Cell Survival; mužské pohlaví; viabilita buněk; steroidní receptory; nádorové buněčné linie; brassinosteroidy; Humans